What Does ‘Having Close Friends from Abroad’ Mean for the Intercultural Competencies: A New View on the Antecedents of Cultural Intelligence - Miroslav Jurásek; Petr Wawrosz (Social Sciences)
The study analyzes the impact of intercultural friendship on cultural intelligence (CQ), which is defined as an individual’s ability to operate effectively in a new intercultural environment. Two hypotheses were tested using an online questionnaire completed in the autumn of 2022 by 358 university students from a private university in Prague, Czech Republic. The participants represented 26 countries, with the majority being Czech nationals. The hypotheses were as follows: (1) overall cultural intelligence, and (2) all its components (metacognitive, cognitive, motivational, and behavioral) would be higher or lower depending on whether individuals had close social ties, operationalized by the binary variable “intercultural friendship”. The first hypothesis was confirmed. However, the second hypothesis was only supported for the motivational and cognitive facets of CQ. Our results indicate that CQ is fundamentally a relational construct, developing primarily through contact with members of other cultures. Contextual factors, such as language skills, travel to foreign countries, residence abroad, and the frequency of intercultural contacts, create situational prerequisites for establishing closer intercultural relationships. However, they do not contribute directly to the development of intercultural skills but rather do so indirectly through these relationships.